THE EFFECT OF LIQUIDITY, SOLVABILITY, PROFITABILITY, AND NON PERFORMING FINANCING ON FIRM VALUE WITH INTELLECTUAL CAPITAL AS MODERATING VARIABLES IN MULTIFINANCE COMPANIES LISTED ON INDONESIA STOCK EXCHANGE IN 2015-2018 - Sitompul, Rifqi (International Journal of Public Budgeting, Accounting and Finance, 2020)
This study aims to analyse the effect of liquidity, solvability, profitability, and non-performing financing on firm value with intellectual capital as a moderating variable. The population in this study amounted to 17 multifinance companies listed on the Indonesia Stock Exchange in 2015-2018, and a sample of 14 companies with purposive sampling technique. Analysis of the data used is panel data regression analysis and interaction testing with the help of the Eviews10 application program. The results of the study showed that all independent variables had a partially negative effect on firm value, where three of the independent variables had no significant effect, namely liquidity, solvability, and non-performing financing while profitability had a significant effect on firm value. Intellectual capital is able to significantly strengthen the effect of liquidity and solvency, and is able to significantly weaken the effect of profitability and non-performing financing.